2015
DOI: 10.4172/2155-9546.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Structural Organization of Skin in Red-Tail Shark(Epalzeorhynchos Bicolor) and Guppy (Poecilia Reticulata)

Abstract: The surface architecture and histological organization of the skin of two ornamental fish; red-tail shark (Epalzeorhynchos bicolor) and guppy (Poecilia reticulata) were the main focus of this study. The skin of the two species was composed of epidermis, dermis and hypodermis, although the epidermis showed great variations in their components in the two species. The epidermis of red-tail shark was consisted of epidermal cells, mucous goblet cells, serous goblet cells, club cells, rodlet cells and melanocytes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…However, as seen in medaka here, club cells are either rare or absent in some of the species examined54849. In aaddition, anti-predator responses have been described in fathead minnows ( Pimephales promelas ) to alarm substance prepared from conspecific larvae that lacked visible club cells50.…”
Section: Discussionmentioning
confidence: 65%
“…However, as seen in medaka here, club cells are either rare or absent in some of the species examined54849. In aaddition, anti-predator responses have been described in fathead minnows ( Pimephales promelas ) to alarm substance prepared from conspecific larvae that lacked visible club cells50.…”
Section: Discussionmentioning
confidence: 65%
“…Rodlet cells are described in different organs. They were detected in the digestive tract [3][4][5][6], pancreases [7], vascular system [8], the bulbus arteriosus [5], kidney tubules [4,6,9] the gonads [10], the skin [7], the epithelium of the operculum and gill raker [11], gill [3,4,6,9], and abdominal cavity among the mesothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Green lines indicate the lineage of nephrosins and pactacins, and the green dotted line indicates the loss of the nephrosin gene in Cichliformes. (Mokhtar, 2015). Therefore, the epithelium morphology is well conserved among cyprinodontiform fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Histological observation indicated that mucus‐secreting cells are scattered in the epithelium of platyfish. Based on the morphology of guppy, which, like the platyfish, belongs to Cyprinodontiformes, mucous cells are located in the epidermis around the head region (Mokhtar, 2015). Therefore, the epithelium morphology is well conserved among cyprinodontiform fishes.…”
Section: Discussionmentioning
confidence: 99%